Perbandingan Kualitas Fisiokimia Kefir Susu Kambing dengan Kefir Susu Sapi (COMPARISON OF PHYSIOCHEMICAL QUALITY OF GOAT MILK KEFIR WITH COW MILK KEFIR) - Sulmiyati, Sulmiyati; Said, Nur Saidah; Fahrodi, Deka Uli; Malaka, Ratmawati; Fatma, Fatma (Jurnal Veteriner; Vol 19 No 2 (2018)DO - 10.19087/jveteriner.2018.19.2.263, 2018)
Kefir is one of the fermented beverages which has a distinctive taste from other fermented milk products. Based on the results of several studies concluded that one that affects the quality of kefir is the milk of being used for. The purpose of this study was to examine the comparison of physiochemical quality of kefir made from goat’s milk and cow’s milk. This study used Completely Randomized Design (CRD) with two treatments and five replications using different milk which was goat’s milk and cow’s milk. Parameters measured were the weight gain of kefir grain (PBBK), ethanol content, the percentage of lactic acid and pH of kefir. The data obtained were analyzed by using the Analysis of Variance and if the treatment was significantly different, then the test continued with the Least Significant Difference (LSD). The results showed that kefir produced with different types of milk showed a significant effect (P <0.05) on pH parameters, lactic acid percentage, and ethanol content, but no significant effect (P>0.05) on the value of PBBK. It can be concluded that the best kefir made of goat milk has characteristics: pH value 3.89, the percentage of lactic acid 0.14; PBBK 26.61%; and 0.72% ethanol content.
Keywords: quality, kefir, goats milk, cows milk